Visual Function Score: A New Clinical Tool to Assess Visual Function and Detect Visual Disorders in Children - Signorini, Sabrina; Luparia, Antonella; Cappagli, Giulia; Perotto, Eleonora; Antonini, Mauro; Morelli, Federica; Aprile, Giorgia; Ballante, Elena; Figini, Silvia; Borgatti, Renato; , VFS Study Group (Frontiers in Pediatrics, 2022)
Introduction: A comprehensive assessment of visual functioning at an early age is important not only for identifying and defining visual impairment but also for planning personalized rehabilitation programs based on the visual diagnosis. Since existing tools to evaluate visual functioning present some important limitations (e.g., they are based on qualitative reports, they do not take into account environmental adaptations of visual testing or they have not been formally validated as clinical instruments), the present work has the main aim to propose a new clinical tool (Visual Function Score, VFS) to detect and define visual disorders at an early age. Methods: The Visual Function Score was administered to one hundred visually impaired children (age range 4 months - 17.7 years old) in the form of a professional-reported protocol for a total of 51 items, each of which is assigned a score from 1 to 9 (or from 0 to 9 in some specific cases). The VFS produces three sub-scores and a global score (from 0 to 100), resulting in a quantitative evaluation of visual functioning. Results: the VFS can detect the well-known differences between different types of visual impairment (cerebral, oculomotor and peripheral or grouped as central and peripheral) and takes into account different environments in the definition of a quantitative score of visual functioning. Discussion: Overall, the use of a quantitative tool to evaluate visual functions and functional vision such as the VFS would be fundamental to monitor the progresses of patients over time in response to rehabilitation interventions.